Audit partner busyness and cost of equity capital. Issue 1 (30th October 2018) - Habib, Ahsan; Bhuiyan, Md. Borhan Uddin; Sun, Xuan (Sean)
Abstract : This paper examines the effects of audit partner busyness on the cost of equity capital. We argue that audit partner busyness affects auditors' work processing accuracy negatively and reduces professional skepticism, thus resulting in higher information risk and, hence, an increased cost of equity capital. Using data from Australian listed companies, we find that the cost of equity capital is indeed higher for firms audited by busy audit partners. However, an additional test documents that this effect is primarily driven by non‐Big 4 observations. Our mediation test results indicate that this positive association is mediated through poor quality financial reporting but is driven by non‐Big 4 observations. Our results are robust to endogeneity concerns emanating from firms' deliberate decisions to choose audit partners. Our study contributes to both the auditing and to the cost of capital literature.